Rare bird documentation form for Northern Goshawk at Hastings, 1983 - Wilson, Barbara L.et al (1983)
Rare bird documentation form for a Northern Goshawk at the John Wilson farm in Hastings in Mills County, IA on November 26, 1983. Epson - sheet feed/flatbed